1998
DOI: 10.1139/f98-078
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory metabolism and swimming performance in growth hormone transgenic Atlantic salmon

Abstract: We show that growth hormone enhanced transgenic salmon have a higher oxygen uptake during routine culture conditions and during forced swimming activity relative to similarly sized control fish. They also have a slightly higher critical oxygen level that limits oxygen uptake. However, they do not differ in regards to critical swimming speed. Growth hormone transgenic Atlantic salmon, Salmo salar, at 12-13°C were an F2 generation using eggs from a transgenic F1 female and milt from a nontransgenic male. They gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
64
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(71 citation statements)
references
References 26 publications
6
64
1
Order By: Relevance
“…and Coho salmon (Oncorhynchus kisutch), were found to have a greater oxygen uptake rate than control fish during routine feeding conditions. Additionally, transgenic fish have a greater daily feed intake in comparison to control fish [42,[46][47][48]. We found that the mean daily feed intake of GH transgenic common carp was 2.12 times greater than control fish during 4 days of feeding.…”
Section: Viability Of Transgenic Fishmentioning
confidence: 61%
See 1 more Smart Citation
“…and Coho salmon (Oncorhynchus kisutch), were found to have a greater oxygen uptake rate than control fish during routine feeding conditions. Additionally, transgenic fish have a greater daily feed intake in comparison to control fish [42,[46][47][48]. We found that the mean daily feed intake of GH transgenic common carp was 2.12 times greater than control fish during 4 days of feeding.…”
Section: Viability Of Transgenic Fishmentioning
confidence: 61%
“…increased food consumption and feeding order, time spent in the feeding areas and the movement level [41]. GH-transgenic salmon are more active [42] and appear more risk-prone than non-transgenic fish, which may potentially increase their mortality from predation in the wild [43][44][45]. The appetite and feeding behavior of transgenic fish increase their competitive ability to obtain food resources, thus enhancing population viability.…”
Section: Viability Of Transgenic Fishmentioning
confidence: 99%
“…Studies of RMR in other transgenic fish species, including coho salmon and Atlantic salmon, found similar results (Stevens et al, 1998;Cook et al, 2000a;Leggatt et al, 2003). Therefore, transgenic fish have demonstrated an elevated routine oxygen uptake in order to meet their metabolic needs.…”
Section: Routine Metabolic Ratementioning
confidence: 77%
“…Other types of GH transgenic fish including Atlantic salmon (S. salar), tilapia (Oreochromis sp.) and coho salmon (O. kisutch), were found to have a greater oxygen uptake rate than control fish during routine feeding conditions (Stevens et al, 1998;Cook et al, 2000a,c;Mckenzie et al, 2003;Leggatt et al, 2003). Additionally, transgenic fish have a greater daily feed intake in comparison to control fish (Fu et al, 1998;Cook et al, 2000b;Rahman et al, 2001;Leggatt et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…(Martinez et al, 1999;Rahman et al, 1998) and common carp (Cyprinus carpio L.) (Wang et al, 2001;Zhong et al, 2012). During recent years, it has become clear that elevated growth hormone (GH) levels in transgenic fish induce a wide range of effects apart from growth promotion (Devlin et al, 1994;Du et al, 1992;Martinez et al, 1996;Nam et al, 2001;Rahman et al, 1998;Wang et al, 2001;Zhong et al, 2012), including altered metabolism (Guan et al, 2008;McKenzie et al, 2003;Stevens et al, 1998), swimming performance (Farrell et al, 1997;Lee et al, 2003;Stevens et al, 1998), anti-predator behavior (Abrahams and Sutterlin, 1999;Duan et al, 2010;Dunham et al, 1999) and growth-related neuroendocrine regulation (Raven et al, 2008). In addition, GH treatment resulted in increased food intake and feeding behavior in normal fish (Johnsson and Bjornsson, 1994).…”
Section: Introductionmentioning
confidence: 99%